Isolation and morphological identification of desert arbuscular mycorhizal fungi from errachidia Region in morocco - KELTOUM OUBELLA,; BOUCHRA OUHMIDOU,; MUSTAPHA AIT CHITT,; MOHIEDDINE MOUMNI, (International Journal of Pharma and Bio Sciences, 2017)
As known the rhizosphere region in the soil is a rich source of microorganism especially Mycorhizal fungi The present study was undertaken in semi-arid areas of Errachidia region in southern Morocco. The objective of the study was to assess the level of root mycorrhization and to identify arbuscular mycorrhizal fungi in palm groves.The highest arbuscular colonization was found in site 1 (83 %) and the lowest was in site 3 (35.7 %). The spore density varies from 120 to 330 spores/100 g of soil, according to the site. Twelve species of arbuscular mycorrhizal fungi were identified in all studied sites. The genera identified were: Acaulospora (6 species), Glomus (5 species), Entrophospora (1 species) and one unidentified species. A great variation in species richness was detected between soil and trap culture in several samples regardless of the origin where samples were performed. Our study demonstrated that AMF have a widespread occurrence in all sites and they sporulate more abundantly in trap cultures than in soil.